2007
DOI: 10.1007/s10722-007-9232-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing phenotypic, biochemical, and molecular diversity in coriander (Coriandrum sativum L.) germplasm

Abstract: Our goals for this research were to elucidate phenotypic and biochemical diversity in coriander (Coriandrum sativum L.) populations maintained at the North Central Regional Plant Introduction Station in Ames, IA, and examine relationships between amplified fragment length polymorphism (AFLP) markers and patterns of phenotypic and biochemical diversity. Phenotypic and biochemical traits were evaluated, and analyses of variance and mean comparisons were performed on the resulting data sets. Euclidean distances f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 65 publications
5
19
0
Order By: Relevance
“…RAPD fragments have not made the expected bands related to the morphological similarity. These similar results have been reported other species [2,7]. …”
Section: Resultssupporting
confidence: 92%
“…RAPD fragments have not made the expected bands related to the morphological similarity. These similar results have been reported other species [2,7]. …”
Section: Resultssupporting
confidence: 92%
“…Of lesser known value is the high composition of petroselinic acid contained within the seed oil. A recent survey of the chemical composition of the known coriander germplasm by Lopez et al [5] reported that the triacylglyceride oil fraction of the seed contains (12.8-30.2%) as shown in highest petroselinate accession (Ames 26819). This rapid growth and maturation make coriander suitable for a double crop rotation through much of the Midwestern US where winter wheat is produced.…”
Section: Coriandermentioning
confidence: 99%
“…Reports on cilantro have evaluated both environmental and genetic factors which influence biomass production of the leaves, quality, and yield of the essential oils (Eyres et al, 2005;Neffati and Marzouk, 2010). Lopez et al (2008) described phenotypic, biochemical and molecular diversity in cilantro populations maintained at the North Central Regional Plant Introduction Station. They assessed significant differences among populations for all the phenotypic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Sativum varieties also have the shortest juvenile period and yield high levels of (E)-2-decenal in seeds (Lopez et al, 2008). Our goal was to study the uptake of nutrients, biomass production and yield of the major compounds in essential oil in leaves of four accessions and one cultivar of cilantro.…”
Section: Introductionmentioning
confidence: 99%